The Correlation Of Seismic P- And S-Waves From Refraction And Downhole Methods For Soil Properties Verification - Anda, Sabrian Tri (2018)
In recognition of the complexities in obtaining in-situ velocity, empirical correlation was established in this study to estimate the in-situ velocities by using seismic refraction. Similarly, there are several difficulties in obtaining seismic refraction S-wave data including its processing. For this reason, empirical correlation was also developed between compressional waves (Vp) and shear waves (Vs) velocities in order to estimate the Vs based on Vp. Furthermore, the correlation between geotechnical and geophysical methods was made to enhance data interpretation and to verify the soil properties. The study was carried out using two seismic methods (refraction and downhole) in two different areas with different geological setting. The first site located at USM Campus, Pulau Pinang which is underlain by granitic rocks, while the second site located at Sungai Batu, Kedah which is underlain by sedimentary rocks. Based on the empirical correlation established in this study, it is found that the downhole data is linearly related with refraction data with R2 values of 0.62 – 0.66.